Lobeglitazone and pioglitazone as add‐ons to metformin for patients with type 2 diabetes: a 24‐week, multicentre, randomized, double‐blind, parallel‐group, active‐controlled, phase III clinical trial with a 28‐week extension. Issue 6 (8th February 2015) - Jin, S.‐M.; Park, C.‐Y.; Cho, Y. M.; Ku, B. J.; Ahn, C. W.; Cha, B.‐S.; Min, K. W.; Sung, Y. A.; Baik, S. H.; Lee, K. W.; Yoon, K.‐H.; Lee, M.‐K.; et al.
Abstract : We aimed to compare the efficacy and safety of lobeglitazone and pioglitazone as add‐ons to metformin in patients with type 2 diabetes. Patients who were inadequately controlled by metformin were randomized and treated once daily with either lobeglitazone (0.5 mg, n = 128) or pioglitazone (15 mg, n = 125) for 24 weeks, with a 28‐week extension trial of lobeglitazone treatment in patients who consented. The primary endpoint was the change in glycated haemoglobin (HbA1c) concentration from baseline to week 24. At week 24, the mean change from baseline in HbA1c was −0.74% for the lobeglitazone group and −0.74% for the pioglitazone group, with a mean difference of 0.01% [95% confidence interval (CI) of difference, −0.16 to 0.18]. The effects of lobeglitazone on lipid variables and the adverse events associated with lobeglitazone were similar to those observed with pioglitazone. Lobeglitazone was not inferior to pioglitazone as an add‐on to metformin in terms of their efficacy and safety.